New distribution record of seagrass Ruppia brevipedunculata from intertidal cultivation ponds in South Kalimantan, Indonesia - DAFIUDDIN SALIM; ROHANI AMBO-RAPPE; SUPRIADI MASHORENG; NADIARTI NURDIN KADIR; MUTA HARAH ZAKARIA; WAWAN KISWARA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Salim D, Ambo-Rappe R, Mashoreng S, Kadir NN, Zakaria MH, Kiswara W. 2025. New distribution record of seagrass Ruppia brevipedunculata from intertidal cultivation ponds in South Kalimantan, Indonesia. Biodiversitas 26: 2088-2096. Ruppia seagrass has a widespread distribution across global waters. The loss of Ruppia in the water highlights the broader environmental challenges faced by coastal ecosystems due to human activities. This study aimed to investigate the distribution of Ruppia brevipedunculata in South Kalimantan Province, Indonesia and identify it using both morphological characteristics and phylogenetic analysis. Samples of Ruppia were randomly collected from cultivation ponds using linear transects of 100 meters in length. The samples were then measured to describe their morphological characteristics. For molecular identification, a total of 200 mg of fresh leaves was isolated using the Plant Genomic DNA Mini Kit and then amplified using the ITS gene sequence, followed by the PCR procedure. DNA analysis was conducted using MEGA 11 software, which involved editing, trimming, and aligning sequences with CLUSTAL W, constructing a phylogenetic tree, and calculating genetic distances. The sample of R. brevipedunculata and other Ruppia sequences were analyzed using the BLAST. The findings revealed that the morphological characteristics of the samples collected in this study closely matched those of R. brevipedunculata recorded in other regions. Furthermore, phylogenetic analysis showed that R. brevipedunculata from this study is closely related to populations from China and Rote Island, Indonesia. This study contributes valuable data on the newly identified distribution record of Ruppia in Indonesian waters and highlights the importance of preserving their habitat in coastal areas.